A STUDY OF ELECTROCHEMICAL CONVERTER FOR A SYSTEM MEASURING THE CONCENTRATION OF HARMFUL SUBSTANCES IN GAS MIXTURES OF THE PAPER - N.R., Yusupbekov; S.M., Gulyamov; B.I., Eshmatova; U.T., Mukhamedkhanov (International Journal of Psychosocial Rehabilitation, 2020)
The paper presents the results of the development and study of the metrological characteristics of measuring transducers of the direct coulometry method—electrochemical cells of direct oxidation of the analyte with a fixed value of its potential on the working electrode, which is used as a gas diffusion hydrophobized electrode. The chosen measurement method provides selective determination of the concentration of almost any substance in the gas mixture by studying and selecting the redox potential of the analyte. The instrument implementation of the coulometric method of gas analysis of the content of toxic substances in industrial process media was carried out, which ensures high efficiency and reliability of the results of continuous monitoring of the composition of natural gas. The device and operation of gas diffusion hydrophobized electrochemical cells of automatic gas analyzers are described.